Production of Neutrophil Extracellular Traps Contributes to the Pathogenesis of Francisella tularemia - Pulavendran, Sivasami; Prasanthi, Maram; Ramachandran, Akhilesh; Grant, Rezabek; Snider, Timothy A.; Chow, Vincent T. K.; Malayer, Jerry R.; Teluguakula, Narasaraju (Frontiers in Immunology, 2020)
Francisella tularensis (Ft) is a highly virulent, intracellular Gram-negative bacterial pathogen. Acute Ft infection by aerosol route causes pneumonic tularemia, characterized by nodular hemorrhagic lesions, neutrophil-predominant influx, necrotic debris, fibrin deposition, and severe alveolitis. Ft suppresses activity of neutrophils by impairing their respiratory burst and phagocytic activity. However, the fate of the massive numbers of neutrophils recruited to the infection site is unclear. Here, we show that Ft infection resulted in prominent induction of neutrophil extracellular traps (NETs) within damaged lungs of mice infected with the live attenuated vaccine strain of Ft (Ft-LVS), as well as in the lungs of domestic cats and rabbits naturally infected with Ft. Further, Ft-LVS infection increased lung myeloperoxidase (MPO) activity, which mediates histone protein degradation during NETosis and anchors chromatin scaffolds in NETs. In addition, Ft infection also induced expression of peptidylarginine deiminase 4, an enzyme that causes citrullination of histones during formation of NETs. The released NETs were found largely attached to the alveolar epithelium, and disrupted the thin alveolar epithelial barrier. Furthermore, Ft infection induced a concentration-dependent release of NETs from neutrophils in vitro. Pharmacological blocking of MPO reduced Ft-induced NETs release, whereas addition of H2O2 (a substrate of MPO) significantly augmented NETs release, thus indicating a critical role of MPO in Ft-induced NETs. Although immunofluorescence and electron microscopy revealed that NETs could efficiently trap Ft bacteria, NETs failed to exert bactericidal effects. Taken together, these findings suggest that NETs exacerbate tissue damage in pulmonary Ft infection, and that targeting NETosis may offer novel therapeutic interventions in alleviating Ft-induced tissue damage.